Enforcement of Health Law: The Large Scale Social Limitation In Indonesia Viewed of The Theory Of Al-Maqashid Asy-Syar’iyyah - Hidayatullah Hidayatullah; Nasrullah Nasrullah (Syariah: Jurnal Hukum dan Pemikiran, 2020)
Abstract